2019
DOI: 10.1055/s-0039-1694738
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Ossified Chronic Subdural Hematoma Complicated with Tension Pneumocephalus

Abstract: A 59-year-old man presented with epileptic seizures interpreted as episodic syncope in the past 3 years and the patient had a history of head trauma about 4 years ago. Computed tomography revealed an ossified chronic subdural hematoma involving the right frontotemporoparietal region, which was totally resected using microsurgical technique. Postoperatively, weakness developed in right arm and magnetic resonance imaging revealed a bilateral tension pneumocephalus, which was immediately treated by a left frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In contrast with other types of SDHs, which are common in the practice of neurosurgery and more prevalent among elderly patients, OSCH typically occurs in children and young adults, as in this case, and is a much rarer entity 1 , 2 . It is reported that only 0.8–10% of CSDH patients develop OSCH 8 . As a consequence, there are no shared or consistent beliefs regarding the clinical approach or the pathophysiology 4 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast with other types of SDHs, which are common in the practice of neurosurgery and more prevalent among elderly patients, OSCH typically occurs in children and young adults, as in this case, and is a much rarer entity 1 , 2 . It is reported that only 0.8–10% of CSDH patients develop OSCH 8 . As a consequence, there are no shared or consistent beliefs regarding the clinical approach or the pathophysiology 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, OSCH patients are usually asymptomatic. However, when OSCH is symptomatic, complaints are not unique and are similar to those of nonossified or noncalcified SDH or any other space-occupying lesion 2 , 8 . Headache is reported as the most common symptom, followed by confusion, drowsiness, dementia, and convulsions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations